2023
DOI: 10.1007/s10584-023-03561-w
|View full text |Cite
|
Sign up to set email alerts
|

“Cooling credits” are not a viable climate solution

Abstract: As the world struggles to limit warming to 1.5 or 2 °C below pre-industrial temperatures, research into solar climate interventions that could temporarily offset some amount of greenhouse gas-driven global warming by reflecting more sunlight back out to space has gained prominence. These solar climate intervention techniques would aim to cool the Earth by injecting aerosols (tiny liquid or solid particles suspended in the atmosphere) into the upper atmosphere or into low-altitude marine clouds. In a new develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…At the same time, with increasing injection rates in the 21st century, compared to the SSP585 scenario, SAI climate engineering would intensify the decrease in precipitation in southern Europe [7,8]. Such a reduction in both temperature and precipitation is mainly because the implementation of SAI climate engineering would alter temporal and spatial distributions of temperature change between day and night, between seasons, and between the tropics and the poles [9]. Jones et al [4], further, found that the implementation of SAI climate engineering would force an increasingly positive phase of the North Atlantic Oscillation (NAO) as the injection rate increased over the course of the 21st century, and cause the Quasi-Biennial Oscillation (QBO) to stall and become locked in a phase with permanent westerly winds in the lower stratosphere [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, with increasing injection rates in the 21st century, compared to the SSP585 scenario, SAI climate engineering would intensify the decrease in precipitation in southern Europe [7,8]. Such a reduction in both temperature and precipitation is mainly because the implementation of SAI climate engineering would alter temporal and spatial distributions of temperature change between day and night, between seasons, and between the tropics and the poles [9]. Jones et al [4], further, found that the implementation of SAI climate engineering would force an increasingly positive phase of the North Atlantic Oscillation (NAO) as the injection rate increased over the course of the 21st century, and cause the Quasi-Biennial Oscillation (QBO) to stall and become locked in a phase with permanent westerly winds in the lower stratosphere [7].…”
Section: Introductionmentioning
confidence: 99%